The Peace Agreement in Colombia in the Light of International Law - OVALLE DIAZ, Nelson Arturo (Université d'Ottawa | University of Ottawa, 2020)
The signing of the peace agreement in 2016 helped put an end to the situation of Non-International Armed Conflict and encourage a stable peace between the Colombian government and the Revolutionary Armed Forces of Colombia – the people’s army (FARC-EP). However, this agreement has created another challenge which is to respect the principle of equality before the law. For revolutionaries to be encouraged to lay down their arms, the State exchanges the possibility of being tried by transitional justice. Legal pluralism helps to explain why the “Special Jurisdiction of Peace” (SJP) may be in conformity with international standards. This article proposes a way to explain the difficult choice between the right to peace and the right to equality before the law by considering international human rights standards. The text suggests the use of constitutional and conventionality judicial reviews as the two appropriate judicial remedies for verifying the compatibility of domestic law with international principles of human rights. These judicial reviews can be used to analyze the invalidity of a national rule that contravenes an international human rights standard based on the principle of supremacy of the imperative international law. Finally, it is concluded that equality before the law is not an absolute dogma and that transitional justice should be the last resort in the case where permanent war is the only other option. As for peace, it is a fundamental right in the international and national legal order, with the intention of guaranteeing the necessary conditions for the respect of other rights and freedoms for all.
Keywords: Peace agreement; Principle of equality; Transitional justice; Colombia; Constitutional; Conventionality; International law